The Influence of Training and Career Development on Employee Performance at PT Adis Dimension Footwear. (Case Study at PT Adis Dimension Footwear Balaraja-Tangerang in the POD (People Organization Development) Division - Juanda , Jujun; Fahmi, Khairul (UJoST- Universal Journal of Science and Technology, 2026)
This study aims to determine the effect of training and career development on employee performance at PT. Adis Dimension Footwear Balaraja Tangerang, especially in the People Organization Development (POD) section. The research method used is quantitative with an associative approach. Data were collected through questionnaires and analyzed using SPSS software version 25. The results showed that the training variable had a significant effect on employee performance, as indicated by the calculated t value > t table (4.657 > 2.00575) and a significance of 0.000 < 0.05. On the other hand, career development did not have a significant effect on employee performance with a calculated t value < t table (1.950 < 2.00575) and a significance of 0.057 > 0.05. However, simultaneously, training and career development had a significant effect on employee performance with a calculated F value > F table (18.232 > 3.18) and a significance of 0.000 < 0.05. Based on these findings, it can be concluded that training is a crucial factor in improving employee performance, while career development requires a more targeted approach to significantly contribute to performance improvement.